Respiratory morbidity in wollastonite workers. Issue 4 (November 1984) - Hanke, W; Sepulveda, M J; Watson, A; Jankovic, J
Abstract : Medical and environmental surveys were conducted at a wollastonite mine and mill in 1976 and in 1982. Health testing included chest radiography, spirometry, and a questionnaire. Workers at a nearby electronics plant were also examined in 1982 for a comparison of lung function and respiratory symptoms. Both wollastonite and control workers showed significant smoking effects for chronic respiratory symptoms, but differences between the groups were not detected. Pneumoconiosis was found in 3% (3/108) of the wollastonite workers in 1982, but none showed a significant progression from their 1976 radiographs. The lung function tests of the 108 wollastonite workers examined in 1982 showed dust related changes in FEV1, FEV1/FVC ratio, and peak flow rate which were independent of age, height, and smoking habit (p less than 0.01). For non-smokers alone, only the FEV1/FVC ratio declined significantly with dust-years of exposure (p less than 0.01). The comparison of lung function in 1982 between a high dust exposed subgroup of wollastonite workers and the control population showed a significantly lower FEV1/FVC ratio and peak flow rate in the study group (p less than 0.05). Analysis of 1976-82 changes in pulmonary function showed that wollastonite workers with higher dust exposure had a significantly greater decline in peak flow over the period than workers with lower exposures (p less than 0.01). These data suggest that long term cumulative exposure to wollastonite may impair ventilatory capacity as reflected by changes in the FEV1/FVC ratio and peak flow rate.